PITCH PROPELLER QUADCOPTER TYPE X AGAINST THRUST AND VOLTAGE MOTOR TO SUPPORT REGIONAL RESILIENCE - Benedictus Mardwianta; Abdul Haris Subarjo; Nurfi Ahmadi; Daniel Setya Budi (Institut Teknologi Dirgantara Adisutjipto, 2022)
The small size of the quadcopter and the low inertia of the drone allows the use of a simple flight control system, with the practicality of the Quadcopter it is hoped that it can be used for disaster management so as to increase regional resilience. Quadcopters issued by the company cannot be changed. This research is done by assembling the quadcopter itself and making changes to the propeller pitch to determine the effect of thrust and thrust motor on a quadcopter type x. From the results of research and calculations carried out, the thrust produced with a 50o pitch angle is greater than the 43o pitch angle for each movement, so the greater the pitch angle, the greater the thrust generated by the propeller. . The voltage that enters each motor will be different depending on its movement. So, the greater the voltage that enters the brushless motor, the higher the rotation of the motor so that the thrust generated is also greater.Â Â